Lean Six Sigma Game App For Android - Lim, Li Zi (Universiti Sains Malaysia, 2018)
Many companies implement lean concept in their production line. Lean knowledge can be transferred more efficiently by using simulation game instead of traditional teaching method. The prime objective of this study is to develop Android games which introduce the lean concept to someone new to the concept as a form of gamified training. Different software has been explored for the most suitable software to be selected as the application platform. Elements of educational and entertainment of the currently existing application are observed. The software which is chosen to develop Android game is MIT App Inventor. For this study, a total of four concepts of lean is chosen to be presented in the game. The concepts are 5S, visual management, Single Minute Exchange of Die (SMED) and simulation of production line. After the games are developed, evaluation of the games is conducted to obtain user opinions. The games are given out to 10 users to be experienced. Feedbacks are received and results are analysed. People with basic lean knowledge can play the games to further enhance their knowledge. The games are both educational and entertaining. Even people who do not have knowledge in lean will be able to grasp the basic knowledge of the mentioned concepts.